2023
DOI: 10.1002/pol.20230649
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning in polymer additive manufacturing: A review

Tahamina Nasrin,
Farhad Pourkamali‐Anaraki,
Amy M. Peterson

Abstract: Additive manufacturing (AM) is a revolutionary technology that enables production of intricate structures while minimizing material waste. However, its full potential has yet to be realized due to technical challenges such as the dependence of part quality on numerous process parameters, the vast number of design options, and the occurrence of defects. These complications may be magnified by the use of polymers and polymer composites due to their complex molecular structures, batch‐to‐batch variations, and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 279 publications
0
1
0
Order By: Relevance
“…Designing and characterizing bio-inks and determining their ideal printing conditions are time-consuming and resource-intensive processes, as they are based on empirical experimentations [ 197 , 198 ]. A number of recent studies indicated that machine learning (ML) can assist in formulating the bio-inks and optimizing the bioprinting conditions which, in turn, reduces the number of required experimentations.…”
Section: Machine Learning In 3d Bioprintingmentioning
confidence: 99%
“…Designing and characterizing bio-inks and determining their ideal printing conditions are time-consuming and resource-intensive processes, as they are based on empirical experimentations [ 197 , 198 ]. A number of recent studies indicated that machine learning (ML) can assist in formulating the bio-inks and optimizing the bioprinting conditions which, in turn, reduces the number of required experimentations.…”
Section: Machine Learning In 3d Bioprintingmentioning
confidence: 99%